UPAYA MENINGKATKAN KREATIVITAS SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROJEK CITIZEN PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS IV MIS WIDYATUL HASANAH - Umi Kalsum; Dinda Yarshal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and apply the citizen project learning model in Pancasilaeducation learning. The study was conducted using the Classroom Action Research(CAR) method with the citizen project learning model through two cycles, with eachcycle including planning, implementation, observation, and reflection. Theinstruments and data collection techniques used in this study were observation,interviews and documentation. The subjects of the study were 18 fourth gradestudents at MIS Widyatul Hasanah Tembung Sukamaju. The results of the studyshowed that in the initial study (pre-cycle) it was known that out of 18 students ingrade IV, there were only 4 students who had high creativity, and 6 students whohad moderate creativity, while 8 students still had creativity that tended to be low.The application of the citizen project learning model in Pancasila education learningin grade IV, namely making a cultural diversity tower. From the implemented project,the students of grade IV were very enthusiastic in following the learning process.The creativity of the students also increased from before the citizen project learningmodel was used. This can be seen from how the students were able to make acultural diversity tower according to their respective creativity. After the citizenproject learning model was implemented to make a cultural diversity tower in (cycleI) from a total of 18 students in grade IV, 9 students had high creativity, 5 studentshad moderate creativity, and only 4 students had low creativity. In the final study(cycle II) it has succeeded in increasing the creativity of students in grade IV from atotal of 18 students who have very high creativity as many as 14 students, and thosewho have moderate creativity as many as 3 students, while those who have low creativity are 1 student. From this it can be said that the citizen project learningmodel has a significant effect on the creativity of grade IV students.